2004
DOI: 10.1002/hyp.5511
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the El Niño–southern oscillation on temperature, precipitation, snow water equivalent and resulting streamflow in the Upper Rio Grande river basin

Abstract: Abstract:Snowmelt runoff dominates streamflow in the Upper Rio Grande (URG) basin of New Mexico and Colorado. Annual variations in streamflow timing and volume at most stations in the region are strongly influenced by the El Niño-southern oscillation (ENSO) through its modulation of the seasonal cycles of temperature and precipitation, and hence on snow accumulation and melting. After removing long-term trends over the study period (water years 1952-99), the dependence of monthly temperature, precipitation, sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A wide variety of trends in streamflow have been detected and attributed to climate change and variability, but a few themes dominate the literature. The most common studies report earlier snowmelt, a shift to earlier streamflow timing, altered spring maximum flows, and/or intensified summer drought (Adam et al , 2009; Barnett et al , 2008; Brabets and Walvoord, 2009; Burn et al , 2010; Cuo et al , 2009; Hamlet et al , 2007; Hodgekins et al , 2003; Hodgekins and Dudley, 2006; Huntington et al , 2004; Jefferson et al , 2008; Knowles et al , 2006; Lee et al , 2004; Mote et al , 2003; Shepherd et al , 2010; Stewart et al , 2005; Stewart, 2009; Wilson et al , 2010; Xu et al , 2009). These studies focus on mountainous regions or near‐polar latitudes of the Northern Hemisphere, and the relationships among warming, snowmelt, and streamflow vary with geographic location, elevation, and latitude.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of trends in streamflow have been detected and attributed to climate change and variability, but a few themes dominate the literature. The most common studies report earlier snowmelt, a shift to earlier streamflow timing, altered spring maximum flows, and/or intensified summer drought (Adam et al , 2009; Barnett et al , 2008; Brabets and Walvoord, 2009; Burn et al , 2010; Cuo et al , 2009; Hamlet et al , 2007; Hodgekins et al , 2003; Hodgekins and Dudley, 2006; Huntington et al , 2004; Jefferson et al , 2008; Knowles et al , 2006; Lee et al , 2004; Mote et al , 2003; Shepherd et al , 2010; Stewart et al , 2005; Stewart, 2009; Wilson et al , 2010; Xu et al , 2009). These studies focus on mountainous regions or near‐polar latitudes of the Northern Hemisphere, and the relationships among warming, snowmelt, and streamflow vary with geographic location, elevation, and latitude.…”
mentioning
confidence: 99%
“…Most studies use the Mann‐Kendall non‐parametric test (Hirsch and Slack, 1984; Helsel and Hirsch, 2002). Moreover, there is broad recognition that trends can be confounded with long‐term climate cycles (Burn, 2008; Huntington et al , 2004; Lee et al , 2004; Marengo, 2009; St. George, 2007; Weider and Boutt, 2010; Woo et al , 2006) and that trends are sensitive to the start date of the record (e.g. Wilby et al , 2008).…”
mentioning
confidence: 99%
“…Forecasting streamflow in the RGHW and URG has largely relied on the ability to represent snow and develop robust statistical relationships between climatology and streamflow. Recent studies have looked at sea‐surface temperature and streamflow (Lee et al 2004; Pascolini‐Campbell et al 2017; Bhandari et al 2019) and shown strong ability to predict streamflow in small headwater basins in the URG (Bhandari et al 2019); however, the relationships are not always consistent or pronounced, especially in the northern parts of the URG, such as the RGHW (Lee et al 2004; Pascolini‐Campbell et al 2017). SNOTEL stations were shown to preferentially represent densely forested areas in the RGHW (Molotch and Bales 2006), and thus changes in forest cover around SNOTEL stations from BBs or wildfire may disrupt existing statistical models.…”
Section: Resultsmentioning
confidence: 99%
“…The researchers [23,56] also discussed that P T may cause changes in W L owing to direct inputs (i.e., channel interception) and by inducing W L from various hydrological stores and pathways. Lee et al [82] showed that annual variations in streamflow timing and volume depend on the seasonal cycles of P T in the upper part of the basin. Thus, P T can affect changes in the temperature and level of stream water as a function of climate variability within a catchment (e.g., [83,84]), even if T F and L R have different correlation patterns.…”
Section: Relationship Between Falling Temperature and Rising Level In...mentioning
confidence: 99%